Peran Etika Bisnis Dan Dukungan Institusional Dalam Mendorong Aktivitas Whistleblowing - Ananda Yuniar, Mecha Zahra (LPPM POLITEKNIK LP3I BANDUNG, 2026)
In the contemporary business environment, significant challenges related to transparency and accountability have emerged. These challenges stem from the prevalence of financial statement fraud cases that conventional oversight methods are unable to address. Whistleblowing has emerged as the primary line of defense, but its effectiveness is often hindered by fear of sanctions, indicating that individual ethical commitment alone is insufficient. The present study aims to integrate aspects of business ethics as a moral foundation and institutional support as a catalyst for protection in encouraging whistleblowing to maintain the integrity of accounting information. Utilizing a literature review approach, the findings substantiate that business ethics functions as an individual moral foundation, while institutional support serves as the primary catalyst that provides protection for whistleblowers. This philosophy of ethics and organizational support has been demonstrated to facilitate the effectiveness of whistleblowing systems in the identification of financial statement fraud. The nexus between ethical values and organizational protection is pivotal to the realization of transparent and accountable corporate governance.